Temporal and spatial distribution of histone acetylation in mouse molar development - Wen Du; Wanyi Luo; Liwei Zheng; Xuedong Zhou; Wei Du (PeerJ)
Histone acetylation is one of the most widely studied histone modification, regulating a variety of biological activities like organ development and tumorigenesis. However, the role of histone acetylation in tooth development is poorly understood. Using the mouse molar as a model, we mapped the distribution patterns of histone H3 and H4, as well as their corresponding acetylation sites during tooth formation in order to unveil the connection between histone acetylation modification and tooth development. Moreover, key histone acetyltransferases and histone deacetylases were detected in both epithelial and mesenchymal cells during tooth development by scRNA-seq and immunohistochemistry. These results suggest that histone acetylation modification functions as an important mechanism in tooth development at different stages.